B-Doped 2D-InSe as a bifunctional catalyst for CO2/CH4 separation under the regulation of an external electric field. Issue 40 (8th October 2021) - Zhao, Chenxu; Xi, Menghui; Huo, Jinrong; He, Chaozheng
Abstract : B@2DInSe is a promising bifunctional catalyst that can separate CO2 and CH4 in response to different electric fields (EFs). Moreover, it can also predict the required EF directly based on functions plotted between E ad [CO2 /CH4 ] and the EF. Abstract : The separation of CO2 or CH4 from a CO2 /CH4 mixture has drawn great attention in relation to solving air pollution and energy shortage issues. However, research into using bifunctional catalysts to separate CO2 and CH4 under different conditions is absent. We have herein designed a novel B-doped two-dimensional InSe (B@2DInSe) catalyst, which can chemically adsorb CO2 with covalent bonds. B@2DInSe can separate CO2 and CH4 in different electric fields, which originates from different regulation mechanisms by an electric field (EF) on the electric properties. The hybridization states between CO2 and B@2DInSe near the Fermi level have experienced gradual localization and eventually merged into a single narrow peak under an increased EF. As the EF further increased, the merged peak shifted towards higher energy states around the Fermi level. In contrast, the EF mainly alters the degree of hybridization between CH4 and B@2DInSe at states far below the Fermi level, which is different from the CO2 situation. These characteristics can also lead to perfect linear relationships between the adsorption energies of CO2 /CH4 and the electric field, which may be beneficial for the prediction of the required EF without large volumes of calculations. Our results have not only provided novel clues for catalyst design, but they have also provided deep understanding into the mechanisms of bifunctional catalysts.